Existential media: Toward a theorization of digital thrownness. (January 2017) - Lagerkvist, Amanda
Our digitally enforced lifeworld is an existential and ambivalent terrain. Questions concerning digital technologies are thus questions about human existence. This theoretical essay employs key concepts from existential philosophy to envision an existential media analysis that accounts for the thrownness of digital human existence. Tracing our digital thrownness to four emergent fields of inquiry, that relate to classic themes (death, time, being there, and being-in-and-with-the-world ), it encircles both mundane connectivity and the extraordinary limit-situations (online) when our human vulnerability is principally felt and our security is shaken. In place of a savvy user, this article posits the "exister" as the principal subject in media studies and inhabitant of the digital ecology—a stumbling, hurting, and relational human being, who navigates within limits and among interruptions through the torrents of our digital existence, in search for meaning and existential security.